PGawean: Aplikasi Mobile Lowongan Pekerjaan Kota Tegal Berbasis Unified Modeling Language (UML) - Somantri, Oman; Wibowo, Dega Surono; Faulin, Muhammad Husni (Teknik Elektro - Politeknik Negeri Semarang, 2018)
The problem experienced by every person is looking for job vacancies. Job vacancy is an information about a job that available for job seekers, especially for a person who have not been employed and/or person who are freshly looking for a job accompanied under certain conditions. One reason of difficulty of getting a job is due to a lack of information about job vacancies. To overcome the problem, there needy urgent to build a system that capable to provide information about job vacancy. The purpose of this research is to build a mobile-based application named